Toi, cyborg ? L’hybridation prothétique dans la nouvelle de science-fiction - Dominique Kunz Westerhoff (ReS Futurae)
While science fiction has disseminated the Cyborg’s concept in an vein of epic heroism, its literary history, from Cordwainer Smith to Martin Caitlin and Frederik Pohl, shows that it challenges constantly its ideal of continuity. From the start, the space opera genre dramatizes the intimate dissonance of the prosthesis and the flesh, the body as an instrument and the loss of the constitutive limits of individuality. These prosthetic incorporations confront the cyborg with an strange sensorium, but also with the traumatic part of the hybridization : the disability comes back with insistence in tragic counter-point of the dream of invulnerability, less to be the object of a technological redemption than as a repressed aspect of posthuman ideologies.Through the cyborg leitmotiv, science fiction reflects also its narrative modalities, themselves prosthetic. The « members » of pre-published short stories enter into romanesque « bodies » that subsume them. Renewing this narrative of concatenation, Eschbach and Bacigalupi elaborate cyborg texts where the limits of the whole and parts, of the one’s own body and its artificial extensions, become confused. In their fictions of hybrid identities, the augmented self becomes another, at the same time singular and shareable.